Hepatoencephalopathy syndrome due to Cassia occidentalis (Leguminosae, Caesalpinioideae) seed ingestion in horses - Oliveira-Filho, J. P. [UNESP]; Cagnini, D. Q. [UNESP]; Badial, P. R. [UNESP]; Pessoa, M. A.; Del Piero, F.; Borges, Alexandre Secorun [UNESP] (Wiley, 2013)
Cassia occidentalis is a bush from the Leguminosae family, subfamily Caesalpinoideae, and is a toxic plant of veterinary interest due to the occasional contamination of animal rations. This report describes the clinical and histopathological findings of an outbreak of C.occidentalis poisoning in horses. Twenty mares were poisoned after consuming ground corn contaminated with 8% of C.occidentalis seeds. Of the 20 animals affected, 12 died: 8 mares were found dead, 2 died 6h after the onset of clinical signs compatible with hepatic encephalopathy and the 2 other animals were subjected to euthanasia 12h after the onset of the clinical signs. The remaining 8 mares presented with mild depression and decreased appetite, but improved with treatment and no clinical sequelae were observed. In 6 animals that underwent a necropsy, an enhanced hepatic lobular pattern was noted and within the large intestine, a large number of seeds were consistently observed. Hepatocellular pericentrolobular necrosis and cerebral oedema were the main histological findings. In one mare, there was mild multifocal semimembranosus rhabdomyocytic necrosis and haemorrhage. Seeds collected from intestinal contents and sifted from the culpable feedstuff were planted. Examination of the leaves, flowers, fruits and seeds of the resultant plants identified C.occidentalis. Horses poisoned by C.occidentalis seeds demonstrate clinical signs associated with hepatoencephalopathy and frequently die suddenly. Lesions primarily involve the liver and secondarily, the central nervous system. Cassia occidentalis poisoning should be considered a differential diagnosis in horses with hepatoencephalopathy and special caution should be taken with horse rations to avoid contamination with seeds of this toxic plant. © 2012 EVJ Ltd.
Keywords: Cassia occidentalis; Hepatoencephalopathy; Horse; Poisoning; plant toxin; animal; animal disease; animal food; chemically induced disorder; chemistry; epidemic; female; food contamination; hepatic encephalopathy; horse; horse disease; maize; plant; plant seed; Senna; Animal Feed; Animals; Disease Outbreaks; Female; Food Contamination; Hepatic Encephalopathy; Horse Diseases; Horses; Plant Poisoning; Plants, Toxic; Seeds; Senna Plant; Zea mays; Animalia; Caesalpinioideae; Equidae; Fabaceae; Senna occidentalis